Customer Re-Use Model of Online Vegetables and Fruit Grocery Platform in Indonesia - Shalihati, Fithriyyah; Jayawinangun, Roni; Rahmatulloh, Febriandi (Jurnal Manajemen & Agribisnis, 2023)
The online customer satisfaction including re-use behaviour concept has been examined in the literature since the development of mobile and digital activity accelerated for the past two years. In order to determine sustainability of online fruit and vegetables grocery platform utilization in practice, not only understanding adoptions but also it is becoming crucial to have detailed understanding of its drivers continuation of re-using behaviour. Unified Theory of Acceptance and Use of Technology (UTAUT) widely used to observe adoptions of technology more specifically online grocery. In this research we will try to use UTAUT used to identify key driving factors of re-use behaviour. We run primary data collection by survey with probabilistic sampling techniques for existing users of top 2 online vegetables and fruit grocery and test the model using hierarchical multiple regression analysis. Sampling is not only conducted for the one that continues to use the platform but also switchers or stop using the services to gain complete understanding and point of view. Several key observations such as expectation, trust, risk, time, enjoyment and innovativeness will become important variables to extend the baseline. Detailed understanding of key driver using behaviour can be utilized as important business metrics to improve customer stickiness and provide personalized offering. Keywords: customer re-use, online grocery platform, utaut, structural equations model